Antarctic Circumpolar Current strength during the late Miocene from IODP Site 383-U1541 - Antje Wegwerth; Helge Wolfgang Arz; Jerome Kaiser; Gisela Winckler; Lester Lembke-Jene; Vincent Rigalleau; Nicoletta Ruggieri; Henrik Sadatzki; Frank Lamy (PANGAEA, 2025)
This dataset presents a record of the Antarctic Circumpolar Current (ACC) strength during the late Miocene from IODP Site 383-U1541 in the Central South Pacific. The drill cores were recovered during IODP 383 expedition "Dynamics of Pacific Antarctic Circumpolar Current (DYNAPACC)" with R/V JOIDES Resolution in 2019 (54° 12.756' S, 125° 25.540' W, 3,604 m water depth; Lamy et al., 2021; doi:10.14379/iodp.proc.383.2021). The ACC strength record represents an extension of the published 5.3 Ma old record of bottom current strength to 8 Ma (Lamy et al., 2024; doi:10.1038/s41586-024-07143-3) and bases on calibrated logarithmic count ratio of the XRF-scanned zirconium to rubidium (ln (Zr/Rb)).